2011
DOI: 10.1016/j.rmr.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of manufactured nanoparticles

Abstract: 2 Résumé :Les nanotechnologies sont définies comme l'ensemble des techniques visant à concevoir, caractériser et produire des matériaux à l'échelle du nanomètre dans au moins l'une de leurs dimensions. Ces nanomatériaux sont eux-mêmes constitués de nano-objets (nanoparticules, nanotubes…). Leur dimension nanométrique leur confère, du fait des lois de la physique quantique, de nouvelles propriétés physicochimiques et des comportements inédits. Les applications des nanotechnologies sont multiples (cosmétologie, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Expanding applications of nanomaterials, particularly carbonaceous nanoparticles (CNP), in new technologies, consumer products and biomedicine, imply their increasing levels of manufacturing. In occupational and environmental settings, the lung is the major portal of unintended CNP entry into the human body potentially leading to pulmonary damage, inflammation, oxidative stress, fibrosis, and granuloma formation 1, 2. In addition, there are numerous attempts to utilize nanoparticles for better delivery of drugs and nucleic acid‐based therapeutics to disease sites in the lung, particularly to the lung epithelium.…”
mentioning
confidence: 99%
“…Expanding applications of nanomaterials, particularly carbonaceous nanoparticles (CNP), in new technologies, consumer products and biomedicine, imply their increasing levels of manufacturing. In occupational and environmental settings, the lung is the major portal of unintended CNP entry into the human body potentially leading to pulmonary damage, inflammation, oxidative stress, fibrosis, and granuloma formation 1, 2. In addition, there are numerous attempts to utilize nanoparticles for better delivery of drugs and nucleic acid‐based therapeutics to disease sites in the lung, particularly to the lung epithelium.…”
mentioning
confidence: 99%
“…may each affect the toxicity profiles [110]. The small size of these new delivery systems imparts them with new physical and chemical properties different from conventional bulk drug powders [111]. It has been observed that multi-walled carbon-nanotube based delivery systems have the capacity to collect in the subpleural regions of the lung, leading to pulmonary fibrosis, multifocal granulomatous inflammation, diffuse histiocytic and neutrophilic inflammation, intra-alveolar lipoproteinosis etc.…”
Section: Fate Of Delivery Systemmentioning
confidence: 99%
“…Although the nanomedicine is fast‐growing for respiratory disease therapy, there are concerns about their potential toxicity, biodegradability, and elimination. The toxicity of nanoparticles on health is determined by size of the nanoparticles, form of the nanoparticles, chemical compositions of nanoparticles, degrees of aggregation, and surface treatment of nanoparticles . In recent studies, it is shown that nanoparticles are more toxic than fine particles .…”
Section: Toxicity Biodegradation and Eliminationmentioning
confidence: 99%
“…In recent studies, it is shown that nanoparticles are more toxic than fine particles . Nanoparticles will deposit in all regions of the respiratory tract, take biological effects on the respiratory system with generation of oxidative stress, pro‐inflammatory and pro‐thrombotic effects, and may develop fibrosis and pulmonary emphysema or DNA damage . Several epidemiologic studies have shown that their side effects can result in morbidity and mortality in susceptible parts of the population …”
Section: Toxicity Biodegradation and Eliminationmentioning
confidence: 99%
See 1 more Smart Citation